Photoinduced radical cascade cyclization of acetylenic acid esters with oxime esters to access cyanalkylated coumarins. Issue 26 (20th June 2022) - Yang, Xiao; Xia, Yanping; Tong, Jinghui; Ouyang, Lu; Lai, Yinlong; Luo, Renshi; Liao, Jianhua
Abstract : Cyanalkylated coumarins via photo-induced radical cascade cyclization of acetylenic acid ester with oxime esters. Experiments evidenced this protocol was accomplished via a radical addition/5- exo spirocyclization/1, 2-ester migration process. Abstract : A photoinduced radical cascade cyclization of acetylenic acid esters with oxime esters is described, providing cyanalkylated coumarins in superior yields under mild conditions. Radical capture and luminescence quenching experiments showed that this transformation was accomplished via a radical addition/5- exo spirocyclization/1, 2-ester migration process.